Behaviour of Acoustic Emission in Deformation and Microcracking Processes of Mg Alloys Matrix Composites Subjected to Compression Tests - , Andrzej Pawełek; , Wojciech Ozgowicz; , Zbigniew Ranachowski; , Stanislav Kúdela; , Andrzej Piątkowski; , Stanislav Kúdela Jr; , Przemysław Ranachowski (Archives of Current Research International, 2017)
Research results on both mechanical and acoustic emission (AE) behavior of Mg-Li and Mg-Al alloys matrix composites (AMC) reinforced with ceramic δ-Al2O3 or carbon fibers subjected to the channel-die compression at room and elevated temperatures are presented in this paper. The AE measurements at room temperature showed that, the effect of anisotropy of the fibres distribution (random planar distribution) with respect to the compression axis appeared in the most investigated composites, whereas the AE activity at 140°C revealed a two- range character and the rate of AE events at 140°C was higher than at room temperature. These effects are discussed in terms of both the differences in thermal expansion between the fibres and the matrix as well as the weakening of the coherency between the fibres and the matrix leading to stronger debonding effects at 140°C than at room temperature. The spectral analysis of AE signals was performed with the Windowed Fourier Transform method, which served to plot the spectral density of AE signal as a function of frequency. The alominous and corundum ceramics types were also investigated in order to illustrate the enhanced AE, which was related to the different crack paths in the final stages of the sample degradation. The results were also discussed on the basis of SEM images, including the in-situ observations of microcracking as well as the dislocation strain mechanisms and microcracking ones during the channel-die compression of the Mg-Li-Al AMC.